Li4Ti5O12 spinel anode: Fundamentals and advances in rechargeable batteries. Issue 4 (26th August 2021) - Zhang, Hao; Yang, Yang; Xu, Hong; Wang, Li; Lu, Xia; He, Xiangming
Abstract: The Li4 Ti5 O12 (LTO) spinel material, ranking at the second large market share after graphite, is a promising anode material for lithium‐ion batteries due to its good cycle stability, rate capability, and safety with both conventional and low‐temperature electrolytes. However, several critical challenges, such as the low capacity and gassing issue, hindered the wide applications of LTO anode. Recent progress indicated that the LTO performances are possible to be further improved by novel strategies, such as heterogeneous phase control, surface engineering, or overlithiation. To rethink and develop advanced LTO anodes, this review intensively associates the performances and modification strategies with the electronics/crystal structures. From a thermodynamic/kinetic point of view, we summarized the data obtained from recently developed characterization techniques, and the results of electrochemical performances and fundamental structures of LTO to potentially address several key challenges and issues toward advanced LTO anodes. As a result, light is shed on the future research direction of the LTO anodes. Abstract : To rethink and develop advanced Li4 Ti5 O12 (LTO) anodes, we intensively associate the properties and new modification strategies with the electronics/crystal structures. From a thermodynamic/kinetic point of view, we focus on the Li + diffusion in various phases, across the interfaces and along the surfaces, and summarize the new characterizations and performances of electrodes and cells, to address key challenges toward advanced LTO anodes.